An Unambiguous Tracking Technique for Cosine-Phased BOC Signals with Low Complexity - Li, Tian; Tang, Zuping; Wei, Jiaolong; Zhou, Zhihui; Wang, Boyi (Společnost pro radioelektronické inženýrství, 2018)
A low-complexity unambiguous tracking method for cosine-phased binary offset carrier (BOCc) signals is proposed in this paper. The proposed method directly constructs a code discriminator function by multiplying two correlation functions. One local reference signal is a specifically designed auxiliary signal whose cross-correlation function with the BOCc signal is an unambiguous S-curve. The other reference signal is a replica BOCc signal whose correlation function with the BOCc signal is used as a "cover" to maintain the slope of the discriminant function as much as possible and to make the final discriminant function non-coherent.The proposed discriminator function has only a single main lock point and can make tracking reliable and unambiguous. In contrast to the traditional unambiguous early-minus-late methods, the proposed method needs only the prompt branch correlator outputs, and the correlation process of the BOCc signal with input signals is the same as that of the carrier loop process. As a result, the proposed method reduces the number of correlators by at least three-quarters. The theoretical analysis and simulation results show that the proposed method has higher code tracking accuracy, lower tracking threshold and better anti-multipath performance than those of PUDLL, SF and SPAR. In conclusion, the proposed method completely eliminates tracking ambiguity, significantly improves tracking performance and reduces implementation complexity.
Keywords: BOC; unambiguous tracking; local auxiliary signal; low complexity; GNSS